Marketing Innovation on Personal Electronic Products - Ismudiar, Wahdan Kukuh; Rufaidah, Popy (School of Business and Management Institut Teknologi Bandung, 2016)
Abstract. In this dynamic era, to keep up with the trends on the market, companies should be able to make innovations. The word â€œinnovationâ€ among electronic companies in peopleâ€™s minds is usually associated with technological aspects of the products. Meanwhile, there is also another aspect of innovation that, over these recent years, has been developed and has also brought significant impacts on the products, which is called Marketing Innovation. In this study, the product is Personal Electronic Products, which include smartphones, tablets, and Laptops that are produced by South Korea and Japanâ€™s electronic companies. The marketing innovation that is implemented by the South Korea and Japanâ€™s electronic companies is measured using five dimensions, which are: Product Design Innovation, Packaging Design Innovation, Product Price Innovation, Product Placement Innovation, and Product Promotion Innovation. The study tests empirically the instrument for multidimensionality, reliability & validity using a confirmatory factor analysis (CFA) approach. The instrument is further found to be reliable, and has convergent and discriminant validity. In order to examine the marketing innovation that is implemented on the personal electronic products of South Korea and Japanâ€™s electronic companies, the study used 250 samples of personal electronic product customers in the area of Bandung City. The result of the study found that the marketing innovation scale is an established measurement to examine the marketing innovation process. From the result, also it can be seen that the customers of South Koreaâ€™s personal electronic products are more perceived with the marketing innovation dimensions that implemented by the South Koreaâ€™s electronic companies on its personal electronic products.Keywords: Marketing innovation, personal electronic product, confirmatory factor analysis